Heterologous expression of C. elegans ion channels in Xenopus oocytes. - Bianchi, Laura (WormBook, 2006)
Physiological methods entered the world of C. elegans, a model system used for many years to study development and a plethora of biological processes mainly employing genetic, molecular and anatomical techniques. One of the methods introduced by physiologists is the use of Xenopus oocytes for expression of C. elegans ion channels. Oocytes of the South African frog Xenopus laevis are used widely for the expression of mammalian channels and transporters contributing to numerous discoveries in these fields. They now promise to aid C. elegans researchers in deciphering mechanisms of channels function and regulation with implications for mammalian patho-physiology. Heterologous cRNA can be easily injected into Xenopus oocytes and translated proteins can be studied using several techniques including electrophysiology, immunocytochemistry and protein biochemistry. This chapter will focus on techniques used for oocyte preparation and injection, and will give a brief overview of specific methods. Limitations of the use of Xenopus oocytes will be also discussed.